Oxidants and antioxidants in hypoxic ischaemic encephalopathy - Thorat, V. N. (Springer India, 2004)
In the present study, the role of serum lipid peroxide and serum nitric oxide as oxidants and erythrocytic superoxide dismutase & serum vitamin E as antioxidants were determined in the 50 neonates with hypoxic ischaemic encephalopathy. (HIE) as against 25 healthy neonates as controls 50 patients of HIE were further divided into two groups i. e. mild and moderate HIE patients. All subjects were in the age group of 37–41 weeks of gestation. The levels of serum lipid peroxide, serum nitric oxide and erythrocytic superoxide dismutase were significantly elevated in both groups of neonates with HIE than those of controls (P<0.001), whereas serum vitamin E levels were significantly decreased in both groups of HIE patients than those of controls (P<0.001). A positive correlation was obtained between serum lipid peroxide and erythrocytic superoxide dismutase (r=+0.86). Alterations in the status of oxidants and antioxidants indicate role of free radicals in the development of HIE.